Surface processing method of diamond-like carbon coating and processing liquid thereof

Through the combination of chemical mechanical polishing technology and sol processing liquid, the low efficiency and low quality problems of diamond-like carbon coatings during ultra-precision processing are solved, and efficient and low-cost surface processing is achieved, which significantly improves the surface quality.

CN119734196APending Publication Date: 2025-04-01TIANJIN RES INST FOR ADVANCED EQUIP TSINGHUA UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411939841.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

When the prior art performs ultra-precision processing of diamond-like carbon coatings, the processing efficiency is low and the surface quality is poor, making it difficult to meet the needs of high precision and high efficiency.

Method used

Chemical mechanical polishing technology is used, combined with sol processing liquid, and the diamond-like carbon coating is polished through chemical and mechanical coupling. The composition of the processing liquid includes silica sol, catalyst, lubricant, surfactant, chelating agent, oxidant and pH adjusting agent.

Benefits of technology

The surface processing efficiency of diamond-like carbon coating is significantly improved, cost is reduced, and good surface quality is obtained, and the surface roughness is significantly reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119734196A_ABST
    Figure CN119734196A_ABST
Patent Text Reader

Abstract

The invention provides a surface processing method of a diamond-like carbon coating and a processing liquid thereof, which are characterized in that chemical and mechanical coupling polishing is performed on the diamond-like carbon coating, and a sol processing liquid is added while mechanical polishing is performed; the polishing load is 200-1500 g / cm < 2 >, and the rotating speed is 10-60 rpm; and the polishing time is 20 to 240 minutes. The invention has the advantages of good dispersibility, strong oxidizability, good processed surface quality, high processing efficiency and the like. The preparation method is simple and convenient in production process, conditions are easy to control, and the processing liquid can improve the surface processing efficiency of the DLC coating and improve the surface quality of the DLC coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hard and brittle material surface processing, and in particular relates to a surface processing method of a diamond-like carbon coating and a processing fluid thereof. Background Art

[0002] Diamond-like Carbon (DLC) coating is a carbon film composed of sp3 bonds and sp2 bonds, which has excellent mechanical properties similar to diamond. Diamond-like carbon is widely used in the fields of automobile, aerospace, mechanical processing, medicine, etc. due to its excellent properties such as high hardness, low friction coefficient, good wear resistance, good corrosion resistance, and small thermal expansion coefficient.

[0003] The advantages of DLC coating such as wear resistance and high hardness also bring about the problem that it is difficult to perform ultra-precision machining. Chemically coupled mechanical polishing technology, as an ultra-precision machining technology that can perform comprehensive flattening, has absolute advantages in surface precision machining of DLC coatings. Chemically coupled mechanical polishing technology uses chemical action to chemically corrode the processed sample to turn it into a product with lower hardness or looseness, and then physically grinds and removes it through mechanical action. However, DLC coatings have the properties of high diamond hardness, stable chemical properties, and wear resistance to a large extent. Therefore, although conventional chemical mechanical polishing technology can flatten DLC coatings, the processing efficiency is low and the surface quality is poor. Therefore, a new type of DLC coating processing fluid is needed to flatten the DLC coating.

[0004] CN101935825A mentions a process for flattening diamond film using diamond-like composite film. The patent uses a polishing process to make the surface roughness of the diamond film Ra <1.5nm. The surface quality still has room for improvement, and the patent does not mention the removal rate. CN111834229A proposes a green and environmentally friendly chemical mechanical polishing method for cadmium zinc telluride wafers. The patent mentions the use of potassium ferrate as an oxidant, but the patent does not mention the improvement effect of potassium ferrate as an oxidant on the polishing liquid, and the processing material cadmium zinc telluride in the patent is a soft and brittle material and cannot be directly applied to the polishing of hard and brittle materials. CN113352230A proposes a method and device for ultra-precision processing of diamond wafers, using potassium ferrate as an oxidant to process graphitized diamonds, but the patent does not study the beneficial data of the oxidant on the improvement of diamond surface quality or removal rate. The patent focuses on the design of equipment for graphitizing diamond surfaces. Therefore, it is necessary to adopt a better chemical mechanical polishing process and use a processing fluid with better oxidizing properties to process the DLC coating in order to improve the processing efficiency and the surface quality of the DLC coating. Invention content

[0005] In view of this, the present invention aims to provide a surface processing method of a diamond-like carbon coating and a processing fluid thereof to solve at least one technical problem in the background technology.

[0006] To achieve the above object, the technical solution created by the present invention is implemented as follows:

[0007] A surface processing method for a diamond-like carbon coating, wherein the diamond-like carbon coating is subjected to chemical and mechanical coupled polishing, and a sol-type processing fluid is added during mechanical polishing;

[0008] The polishing load is 200~1500g / cm 2 , the speed is between 10 and 60 rpm;

[0009] The polishing time is 20 to 240 minutes.

[0010] Furthermore, the polishing load is 1200 g / cm 2 ;

[0011] And / or, the polishing speed is 40 rpm;

[0012] And / or, the polishing time is 120 minutes.

[0013] Furthermore, the sol-type processing fluid includes, by mass percentage: 1-40% silica sol, 0.1-5% catalyst, 1-10% lubricant, 0.1-5% surfactant, 0.02-2% chelating agent, 0.1-10% oxidant, 0.2-2% pH adjuster, and the balance is deionized water.

[0014] Further, the oxidant includes one or more of hydrogen peroxide, potassium permanganate, potassium ferrate or sodium hypochlorite.

[0015] Furthermore, the catalyst includes one or both of a metal element or a metal compound.

[0016] Furthermore, the metal in the metal element or metal compound includes one or more of iron, manganese, nickel, vanadium, copper, and chromium.

[0017] Furthermore, the lubricant is a polymer polyether, preferably, the polymer polyether includes one or more of polyoxypropylene oxyethylene glycerol ether, propylene glycol block polyether, polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer, trans block polyether, fatty alcohol polyoxyethylene ether, fatty alcohol polyoxypropylene ether, and linear alcohol polyoxyethylene ether.

[0018] The chelating agent includes one or more of phosphates, aminocarboxylic acids, hydroxycarboxylic acids, and organic amines.

[0019] Furthermore, the pH adjuster includes one or more of hydrochloric acid, nitric acid, citric acid, lactic acid, sulfuric acid, sodium hydroxide, potassium hydroxide, and ammonia water.

[0020] The preparation method of the sol-type processing fluid is as follows: at room temperature, silica sol, lubricant, surfactant, chelating agent and deionized water are mixed, stirred evenly, and then an oxidant, a catalyst and a pH adjuster are added in sequence and stirred evenly, and the mixture is placed in a liquid storage tank to obtain the sol-type processing fluid.

[0021] Compared with the prior art, the surface processing method of a diamond-like carbon coating and the processing fluid thereof created by the present invention have the following advantages:

[0022] 1. The preparation process of the DLC coating surface processing fluid provided in this application is simple, and the processing process does not involve high temperature and high pressure, and the process is safe.

[0023] 2. The DLC coating surface processing fluid provided in this application can improve the DLC coating surface processing efficiency and reduce costs.

[0024] 3. The DLC coating surface processing fluid provided in this application can obtain good surface quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments and descriptions of the present invention are used to explain the present invention and do not constitute an improper limitation on the present invention. In the drawings:

[0026] Figure 1 This is the surface morphology of the DLC coating of the present application (A is the initial surface morphology of the DLC coating, and its surface roughness Ra is 4.690nm, and B is the surface morphology of the DLC coating described in Example 10 after polishing, and its surface roughness Ra is 0.168nm after testing). DETAILED DESCRIPTION

[0027] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0028] The present invention will be described in detail below with reference to the accompanying drawings and in combination with embodiments.

[0029] Example 1

[0030] The abrasive is silica sol, with a mass percentage of 25%, the catalyst is iron oxide, with a mass percentage of 10%, the oxidant is hydrogen peroxide, with a mass percentage of 1%, the lubricant is polyether 1720 and fatty alcohol polyoxyethylene ether JFC-6, with mass percentages of 1% and 2% respectively, the chelating agent is EDTA, with a mass percentage of 0.5%, the pH adjuster is sulfuric acid and potassium hydroxide to adjust the pH value to 9.5, and the balance is deionized water.

[0031] Polishing process load is 1200g / cm 2 , the speed is 40rpm, and the time is 120min. After chemical mechanical polishing of the DLC coating, the material removal rate is 84.4nm / h and the surface roughness is 0.995nm.

[0032] Example 2

[0033] The abrasive is silica sol, with a mass percentage of 25%, the catalyst is iron oxide, with a mass percentage of 10%, the oxidant is hydrogen peroxide, with a mass percentage of 1%, the lubricant is polyether 1740 and fatty alcohol polyoxyethylene ether JFC-6, with mass percentages of 1% and 2% respectively, the chelating agent is EDTA, with a mass percentage of 0.5%, the pH adjuster is sulfuric acid and potassium hydroxide to adjust the pH value to 9.5, and the balance is deionized water.

[0034] Polishing process load is 1200g / cm 2 , the speed is 40rpm, and the time is 120min. After chemical mechanical polishing of the DLC coating, the material removal rate is 85.6nm / h and the surface roughness is 0.904nm.

[0035] Example 3

[0036] The abrasive is silica sol, with a mass percentage of 25%, the catalyst is iron oxide, with a mass percentage of 10%, the oxidant is hydrogen peroxide, with a mass percentage of 1%, the lubricant is polyether L62 and fatty alcohol polyoxyethylene ether JFC-6, with a mass percentage of 1% and 2% respectively, the chelating agent is EDTA, with a mass percentage of 0.5%, the pH adjuster is sulfuric acid and potassium hydroxide to adjust the pH value to 9.5, and the balance is deionized water.

[0037] Polishing process load is 1200g / cm 2 , the speed is 40rpm, and the time is 120min. After chemical mechanical polishing of the DLC coating, the material removal rate is 86.4nm / h and the surface roughness is 0.765nm.

[0038] Example 4

[0039] The abrasive is silica sol, with a mass percentage of 25%, the catalyst is iron oxide, with a mass percentage of 10%, the oxidant is hydrogen peroxide, with a mass percentage of 1%, the lubricant is polyether L62 and linear alcohol polyoxyethylene ether TA30, with mass percentages of 1% and 2% respectively, the chelating agent is EDTA, with a mass percentage of 0.5%, the pH adjuster is nitric acid and sodium hydroxide to adjust the pH value to 9.5, and the balance is deionized water.

[0040] Polishing process load is 1200g / cm 2 , the rotation speed is 40rpm, the time is 120min, the material removal rate of the DLC coating after chemical mechanical polishing is 92.7nm / h, and the surface roughness is 0.823nm.

[0041] Example 5

[0042] The abrasive is silica sol, with a mass percentage of 25%, the catalyst is iron oxide, with a mass percentage of 10%, the oxidant is hydrogen peroxide, with a mass percentage of 1%, the lubricant is polyether L62 and fatty alcohol polyoxypropylene ether DM50, with mass percentages of 1% and 2% respectively, the chelating agent is EDTA, with a mass percentage of 0.5%, the pH adjuster is sulfuric acid and sodium hydroxide to adjust the pH value to 9.5, and the balance is deionized water.

[0043] Polishing process load is 1200g / cm 2 , the speed is 40rpm, and the time is 120min. After chemical mechanical polishing of the DLC coating, the material removal rate is 93.5nm / h and the surface roughness is 0.696nm.

[0044] Example 6

[0045] The abrasive is silica sol, with a mass percentage of 25%, the catalyst is iron oxide, with a mass percentage of 10%, the oxidant is hydrogen peroxide, with a mass percentage of 1%, the lubricant is polyether L62 and DM50, with a mass percentage of 1% and 2% respectively, the chelating agent is polyvinyl alcohol, with a mass percentage of 0.5%, the pH adjuster is sulfuric acid and potassium hydroxide to adjust the pH value to 9.5, and the balance is deionized water.

[0046] Polishing process load is 1200g / cm 2 , the rotation speed is 40rpm, the time is 120min, and after the DLC coating is subjected to chemical mechanical polishing, the material removal rate is 95.1nm / h and the surface roughness is 0.673nm.

[0047] Example 7

[0048] The abrasive is silica sol, with a mass percentage of 25%, the catalyst is iron oxide, with a mass percentage of 10%, the oxidant is hydrogen peroxide, with a mass percentage of 1%, the lubricant is polyether L62 and DM50, with a mass percentage of 1% and 2% respectively, the chelating agent is glycine, with a mass percentage of 0.5%, the pH adjuster is sulfuric acid and potassium hydroxide to adjust the pH value to 9.5, and the balance is deionized water.

[0049] Polishing process load is 1200g / cm 2 , the rotation speed is 40rpm, the time is 120min, and after the DLC coating is subjected to chemical mechanical polishing, the material removal rate is 108.2nm / h and the surface roughness is 0.473nm.

[0050] Example 8

[0051] The abrasive is silica sol with a mass percentage of 25%, the catalyst is metal metavanadate with a mass percentage of 10%, the oxidant is hydrogen peroxide with a mass percentage of 1%, the lubricant is polyether L62 and DM50 with a mass percentage of 1% and 2% respectively, the chelating agent is glycine with a mass percentage of 0.5%, the pH adjuster is sulfuric acid and potassium hydroxide with a pH value of 9.5, and the balance is deionized water.

[0052] Polishing process load is 1200g / cm 2 , the rotation speed is 40rpm, the time is 120min, and after the DLC coating is subjected to chemical mechanical polishing, the material removal rate is 161.2nm / h and the surface roughness is 0.209nm.

[0053] Example 9

[0054] The abrasive is silica sol with a mass percentage of 25%, the catalyst is metal metavanadate with a mass percentage of 10%, the oxidant is sodium hypochlorite with a mass percentage of 1%, the lubricant is polyether L62 and DM50 with a mass percentage of 1% and 2% respectively, the chelating agent is glycine with a mass percentage of 0.5%, the pH adjuster is sulfuric acid and potassium hydroxide with a pH value of 9.5, and the balance is deionized water.

[0055] Polishing process load is 1200g / cm 2 , the rotation speed is 40rpm, the time is 120min, and after the DLC coating is subjected to chemical mechanical polishing, the material removal rate is 221.5nm / h and the surface roughness is 0.287nm.

[0056] Example 10

[0057] The abrasive is silica sol, with a mass percentage of 25%, the oxidant is ferrate metal salt, with a mass percentage of 1%, the lubricant is polyether L62 and DM50, with a mass percentage of 1% and 2% respectively, the chelating agent is glycine, with a mass percentage of 0.5%, the pH adjuster is sulfuric acid and potassium hydroxide adjusted to a pH value of 9.5, and the balance is deionized water.

[0058] Polishing process load is 1200g / cm 2 , the rotation speed is 40rpm, the time is 120min, and after the DLC coating is subjected to chemical mechanical polishing, the material removal rate is 586.3nm / h and the surface roughness is 0.168nm.

[0059] Embodiment 11

[0060] The abrasive is silica sol, with a mass percentage of 25%, the oxidant is a mixture of hydrogen peroxide and ferrate metal salt, added in a ratio of 3:1, with a mass percentage of 1%, the lubricant is polyether L62 and DM50, with mass percentages of 1% and 2% respectively, the chelating agent is glycine, with a mass percentage of 0.5%, the pH adjuster is sulfuric acid and potassium hydroxide adjusted to a pH value of 9.5, and the balance is deionized water.

[0061] Polishing process load is 1200g / cm 2 , the rotation speed is 40rpm, the time is 120min, and after the DLC coating is subjected to chemical mechanical polishing, the material removal rate is 234.4nm / h and the surface roughness is 0.241nm.

[0062] Comparative Example 1

[0063] The DLC coating was polished using a commercially available silica sol chemical mechanical polishing solution with a polishing process load of 1200 g / cm 2 , the speed is 40rpm, the time is 120min, the surface roughness Ra of DLC after polishing is 1.223nm, and the material removal rate is 67.7nm / h

[0064] Comparative Example 2

[0065] The abrasive is silica sol, with a mass percentage of 25%, the oxidant is hydrogen peroxide, with a mass percentage of 1%, and the balance is deionized water.

[0066] Polishing process load is 1200g / cm 2 , the rotation speed is 40rpm, the time is 120min, and after the DLC coating is subjected to chemical mechanical polishing, the material removal rate is 52.5nm / h and the surface roughness is 3.544nm.

[0067] Comparative Example 3

[0068] The abrasive is silica sol with a mass percentage of 25%, the oxidant is hydrogen peroxide with a mass percentage of 1%, the lubricant is polyether 1720 with a mass percentage of 0.8%, and the balance is deionized water.

[0069] Polishing process load is 1200g / cm 2 , the rotation speed is 40rpm, the time is 120min, and after the DLC coating is subjected to chemical mechanical polishing, the material removal rate is 52.8nm / h and the surface roughness is 2.648nm.

[0070] Comparative Example 4

[0071] The abrasive is silica sol with a mass percentage of 25%, the oxidant is hydrogen peroxide with a mass percentage of 1%, the lubricant is polyether 1720 and JFC-6 with a mass percentage of 0.8% and 2% respectively, and the balance is deionized water.

[0072] Polishing process load is 1200g / cm 2 , the rotation speed is 40rpm, the time is 120min, and after the DLC coating is subjected to chemical mechanical polishing, the material removal rate is 65.3nm / h and the surface roughness is 1.036nm.

[0073] Comparative Example 5

[0074] The abrasive is silica sol with a mass percentage of 25%, the oxidant is hydrogen peroxide with a mass percentage of 1%, the lubricant is polyether 1720 and JFC-6 with a mass percentage of 0.8% and 2% respectively, the chelating agent is EDTA with a mass percentage of 1.2%, and the balance is deionized water.

[0075] Polishing process load is 1200g / cm 2 , the rotation speed is 40rpm, the time is 120min, and after the DLC coating is subjected to chemical mechanical polishing, the material removal rate is 66.1nm / h and the surface roughness is 1.044nm.

[0076] Comparative Example 6

[0077] The abrasive is silica sol, with a mass percentage of 25%, the catalyst is iron oxide, with a mass percentage of 10%, the oxidant is hydrogen peroxide, with a mass percentage of 1%, the lubricant is JFC-6, with a mass percentage of 2%, the chelating agent is EDTA, with a mass percentage of 0.5%, the pH adjuster is sulfuric acid and potassium hydroxide adjusted to a pH value of 9.5, and the balance is deionized water.

[0078] Polishing process load is 1200g / cm 2, the rotation speed is 40rpm, the time is 120min, and after the DLC coating is subjected to chemical mechanical polishing, the material removal rate is 83.5nm / h and the surface roughness is 1.165nm.

[0079] Comparative Example 7

[0080] The abrasive is silica sol, with a mass percentage of 25%, the catalyst is iron oxide, with a mass percentage of 10%, the oxidant is hydrogen peroxide, with a mass percentage of 1%, the lubricant is polyether 1720, with a mass percentage of 1%, the chelating agent is EDTA, with a mass percentage of 0.5%, the pH adjuster is sulfuric acid and potassium hydroxide to adjust the pH value to 9.5, and the balance is deionized water.

[0081] Polishing process load is 1200g / cm 2 , the rotation speed is 40rpm, the time is 120min, and after the DLC coating is subjected to chemical mechanical polishing, the material removal rate is 79.5nm / h and the surface roughness is 1.044nm.

[0082] Comparative Example 8

[0083] The abrasive is silica sol, with a mass percentage of 25%, the catalyst is iron oxide, with a mass percentage of 10%, the oxidant is hydrogen peroxide, with a mass percentage of 1%, the lubricant is polyether 1720 and fatty alcohol polyoxyethylene ether JFC-6, with mass percentages of 1% and 2% respectively, the pH adjuster is sulfuric acid and potassium hydroxide to adjust the pH value to 9.5, and the balance is deionized water.

[0084] Polishing process load is 1200g / cm 2 , the rotation speed is 40rpm, the time is 120min, and after the DLC coating is subjected to chemical mechanical polishing, the material removal rate is 86.8nm / h and the surface roughness is 0.954nm.

[0085] Comparative Example 9

[0086] The abrasive is silica sol, with a mass percentage of 25%, the catalyst is iron oxide, with a mass percentage of 10%, the oxidant is hydrogen peroxide, with a mass percentage of 1%, the chelating agent is EDTA, with a mass percentage of 0.5%, the pH adjuster is sulfuric acid and potassium hydroxide adjusted to a pH value of 9.5, and the balance is deionized water.

[0087] Polishing process load is 1200g / cm 2 , the rotation speed is 40rpm, the time is 120min, and after the DLC coating is subjected to chemical mechanical polishing, the material removal rate is 70.4nm / h and the surface roughness is 1.812nm.

[0088] Comparative Example 10

[0089] The abrasive is silica sol with a mass percentage of 25%, the catalyst is iron oxide with a mass percentage of 10%, the oxidant is hydrogen peroxide with a mass percentage of 1%, the lubricant is polyether 1720 with a mass percentage of 1%, the pH adjuster is sulfuric acid and potassium hydroxide with the pH value adjusted to 9.5, and the balance is deionized water.

[0090] Polishing process load is 1200g / cm 2 , the rotation speed is 40rpm, the time is 120min, and after the DLC coating is subjected to chemical mechanical polishing, the material removal rate is 75.4nm / h and the surface roughness is 2.107nm.

[0091] Comparative Example 11

[0092] The abrasive is silica sol, with a mass percentage of 25%, the catalyst is iron oxide, with a mass percentage of 10%, the oxidant is hydrogen peroxide, with a mass percentage of 1%, the lubricant is fatty alcohol polyoxyethylene ether JFC-6, with a mass percentage of 2%, the pH adjuster is sulfuric acid and potassium hydroxide adjusted to a pH value of 9.5, and the balance is deionized water.

[0093] Polishing process load is 1200g / cm 2 , the rotation speed is 40rpm, the time is 120min, and after the DLC coating is subjected to chemical mechanical polishing, the material removal rate is 77.6nm / h and the surface roughness is 1.454nm.

[0094] Through Example 1, Comparative Examples 2, 3, 4, 6, 7, 9, 10, and 11, it can be seen that adding different types of lubricants to the polishing liquid can improve the surface quality of the DLC coating. This is because the polyether additive can play the role of lubricant and surfactant at the same time. The lubricant can improve the lubrication performance of the polishing liquid, reduce mechanical wear and temperature rise during polishing, thereby improving the surface quality of the DLC coating; the surfactant can improve the dispersion and suspension performance of the abrasive, and the uniformly dispersed abrasive can increase the polishing area, uniform polishing pressure, and improve the removal rate and surface quality. Then, through Examples 1, 2, 3, 4, 5, and 10, the effects of different lubricants are compared. The type, amount, and compound of the lubricant can affect the removal rate of the DLC coating. Among them, the addition of polyether L62 can significantly improve the surface quality of the DLC coating, and the addition of DM50 can increase the material removal rate. The mixture of the two polyethers can balance the lubricity and surface activity in the system, further improve the surface quality of the diamond-like carbon coating, and achieve high-precision and high-rate removal of the coating.

[0095] Comparative Examples 4 and 5 show that adding a chelating agent to the polishing liquid has no significant effect on improving the surface quality and material removal rate of the DLC coating. This is because there is no metal ion in the system and the chelating agent does not play a role. Example 1 and Comparative Example 8 compare the effect of adding a chelating agent on the polishing of the DLC coating in the presence of metal ions. The chelating agent can significantly improve the removal rate and surface quality in the presence of metal ions. This is because the chelating agent can chelate metal ions to make them exist in the form of organic metals, thereby reducing the adhesion of metal ions on the polishing surface and reducing the mechanical wear of the polishing surface. Then Examples 5, 6, and 7 compare the effects of different chelating agents. The experimental results show that glycine has the best effect.

[0096] By comparing the effects of different catalysts on improving the removal rate and surface quality of the DLC coating through Examples 7 and 8, it can be seen that the addition of the catalyst can further improve the material removal rate. This is because the presence of the catalyst can catalyze the activity of hydrogen peroxide, further improving the chemical corrosion of the DLC coating and improving the removal rate.

[0097] Through Examples 8, 9, 10 and 11, the polishing effect of DLC coating under different oxidants was studied, and it was found that the strong oxidizing property of potassium ferrate can not only improve the material removal rate but also improve the surface quality, and the combination of hydrogen peroxide and potassium ferrate has no synergistic effect.

[0098] It can be seen from Example 1 and Comparative Example 9 that after the lubricant and surfactant are compounded in the polishing liquid, the removal rate of the DLC coating is increased by 19.89%, and the surface roughness is reduced from 1.812 nm to 0.995 nm.

[0099] It can be seen from Example 1 and Comparative Example 10 that after the surfactant and the chelating agent are compounded in the polishing liquid, the removal rate of the DLC coating is increased by 11.94%, and the surface roughness is reduced from 2.107 nm to 0.995 nm.

[0100] It can be seen from Example 1 and Comparative Example 11 that after the lubricant and the chelating agent are compounded in the polishing liquid, the removal rate of the DLC coating is increased by 8.76%, and the surface roughness is reduced from 1.454 nm to 0.995 nm.

[0101] Comparative Examples 2 and 5 show that the three additives of lubricant, surfactant and chelating agent have a synergistic effect after being compounded, which can increase the removal rate by 25.90% and reduce the surface roughness by 70.62%.

[0102] By comparing the polishing effects of commercially available silica sol chemical mechanical polishing fluid and homemade DLC coating processing fluid, it can be seen that the material removal rate and surface quality of the homemade processing fluid are better than those of the commercially available polishing fluid.

[0103] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A surface processing method for a diamond-like carbon coating, characterized in that: Chemical and mechanical coupled polishing is performed on the diamond-like carbon coating, and a sol-type processing fluid is added during mechanical polishing; The polishing load is 200~1500g / cm 2 , the speed is 10~60rpm, and the time is 20~240min.

2. The surface processing method of a diamond-like carbon coating according to claim 1, characterized in that: The polishing load is 1200g / cm 2 ; And / or, the polishing speed is 40 rpm; And / or, the polishing time is 120 minutes.

3. The sol-type processing fluid used in the surface processing method of a diamond-like carbon coating according to claims 1-2, characterized in that: The sol processing fluid includes, by mass percentage, 1-40% silica sol, 0.1-5% catalyst, 1-15% lubricant, 0.02-2% chelating agent, 0.1-10% oxidant, 0.2-2% pH adjuster, and the balance is deionized water.

4. The sol-type processing fluid according to claim 3, characterized in that: The oxidizing agent includes one or more of hydrogen peroxide, potassium permanganate, potassium ferrate or sodium hypochlorite.

5. The sol-type processing fluid according to claim 3, characterized in that: The catalyst includes one or both of a metal element or a metal compound.

6. The sol-type processing fluid according to claim 5, characterized in that: The metal in the metal element or metal compound includes one or more of iron, manganese, nickel, vanadium, copper, and chromium.

7. The sol-type processing fluid according to claim 3, characterized in that: The lubricant is a polymer polyether. Preferably, the polymer polyether includes one or more of polyoxypropylene oxyethylene glycerol ether, propylene glycol block polyether, polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer, trans block polyether, fatty alcohol polyoxyethylene ether, fatty alcohol polyoxypropylene ether, and linear alcohol polyoxyethylene ether.

8. The sol-type processing fluid according to claim 3, characterized in that: The chelating agent includes one or more of phosphates, aminocarboxylic acids, hydroxycarboxylic acids, and organic amines.

9. The sol-type processing fluid according to claim 3, characterized in that: The pH adjuster includes one or more of hydrochloric acid, nitric acid, citric acid, lactic acid, sulfuric acid, sodium hydroxide, potassium hydroxide, and ammonia water.

10. The method for preparing a sol-type processing fluid according to any one of claims 3 to 9, characterized in that: At room temperature, silica sol, lubricant, surfactant, chelating agent and deionized water are mixed, stirred evenly, then oxidant, catalyst and pH adjuster are added in sequence and stirred evenly, and placed in a liquid storage tank to obtain a sol processing fluid.

Citation Information

Patent Citations

  • Process for flattening diamond film by utilizing compound diamond-like carbon (DLC) film

    CN101935825A

  • Green and environment-friendly chemical mechanical polishing method for cadmium zinc telluride wafer

    CN111834229A

  • Diamond wafer ultra-precision machining method and device

    CN113352230A